Stability of Mixed Type Cubic and Quartic Functional Equations in Random Normed Spaces - M. Eshaghi Gordji; M. B. Savadkouhi (Journal of Inequalities and Applications, 2009)
We obtain the stability result for the following functional equation in random normed spaces (in the sense of Sherstnev) under arbitrary t-norms f(x+2y)+f(x−2y)=4[f(x+y)+f(x−y)]−24f(y)−6f(x)+3f(2y).